The current regenerative medicine approaches of craniofacial diseases: A narrative review - Tahmasebi, Elahe; Mohammadi, Mehdi; Alam, Mostafa; Abbasi, Kamyar; Gharibian Bajestani, Saeed; Khanmohammad, Rojin; Haseli, Mohsen; Yazdanian, Mohsen; Esmaeili Fard Barzegar, Peyman; Tebyaniyan, Hamid (Frontiers in Cell and Developmental Biology, 2023)
Craniofacial deformities (CFDs) develop following oncological resection, trauma, or congenital disorders. Trauma is one of the top five causes of death globally, with rates varying from country to country. They result in a non-healing composite tissue wound as they degenerate in soft or hard tissues. Approximately one-third of oral diseases are caused by gum disease. Due to the complexity of anatomical structures in the region and the variety of tissue-specific requirements, CFD treatments present many challenges. Many treatment methods for CFDs are available today, such as drugs, regenerative medicine (RM), surgery, and tissue engineering. Functional restoration of a tissue or an organ after trauma or other chronic diseases is the focus of this emerging field of science. The materials and methodologies used in craniofacial reconstruction have significantly improved in the last few years. A facial fracture requires bone preservation as much as possible, so tiny fragments are removed initially. It is possible to replace bone marrow stem cells with oral stem cells for CFDs due to their excellent potential for bone formation. This review article discusses regenerative approaches for different types of craniofacial diseases.